Activity of ceftolozane/tazobactam and comparators against gram-negative bacilli: Results from the Study for Monitoring Antimicrobial Resistance Trends (SMART – Brazil), 2018‒2021 - Amanda Azevedo Bittencourt; Vinicius Lima Faustino; Paula de Mendonça Batista; Lays Paulino Leonel; Marina Della Negra de Paula; Thales José Polis (Brazilian Journal of Infectious Diseases)
Increased spread of antimicrobial resistance by Gram-Negative Bacilli (GNB) poses a global challenge, with exacerbated burden post-pandemic. The aim of this study was to investigate the in vitro activity of ceftolozane/tazobactam and its comparators against the frequently identified GNB isolated from patients admitted to Brazilian medical sites between the year 2018‒2019 and 2020‒2021. The impact of pandemic on antimicrobial resistance and presence of β-lactamase genes were also evaluated. Antimicrobial susceptibility testing and molecular characterization of ß-lactamase encoding genes using Polymerase Chain Reaction (PCR) and DNA sequencing were carried out from GNB isolated mostly from intra-abdominal, respiratory, and urinary tract infections and interpreted following BrCAST/EUCAST guidelines. A total of 3994 GNB isolates were evaluated which mostly included E. coli, K. pneumoniae and P. aeruginosa. Ceftolozane/tazobactam remained highly active against E. coli isolates during both 2018‒2019 (96.0 %) and 2020‒2021 (98.5 %). Among K. pneumoniae, ceftolozane/tazobactam (47.6 % and 43.0 % susceptible during 2018‒2019 and 2020‒2021, respectively) showed poor activity due to blaKPC-2. Colistin and ceftolozane/tazobactam were the most active β-lactam agents tested against P. aeruginosa in 2018‒2019 (99.3 % and 88.8 %) and 2020‒2021 (100 % and 92.8 %), including ceftazidime and meropenem resistant isolates. β-lactamase encoding gene characterization was carried out and both carbapenemases and Extended-Spectrum β-Lactamase (ESBL) producers were found in E. coli, K. pneumoniae and P. aeruginosa isolates. Ceftolozane/tazobactam documented remarkable in vitro activity against E. coli and P. aeruginosa isolates in Brazil, both pre- and post-pandemic periods and could constitute an effective therapeutic option for the treatment of urinary tract infections, intra-abdominal infections, and respiratory tract infections.